Fetal Abdominal Cyst as a Stage of Meconium Peritonitis after Fetoscopic Laser Photocoagulation - Tsikhanenka, Iryna; Beluga, Maxim; Semenchuk, Venera; Kurlovich, Ivan; Marahovskaya, Ella (Journal of Fetal Medicine, 2023)
Fetal meconium peritonitis (FMP) is a rare form of sterile chemical peritonitis occurring in utero due to the perforation of the fetal intestine, sometimes after fetoscopic laser photocoagulation (FLP) in twin-to-twin transfusion syndrome, with the broad spectrum of prenatal ultrasound manifestations including abdominal cyst. We report a unique presentation of FMP following FLP with ascites, pseudocyst formation, and the cyst resolving probably of a fistula formation. This case report highlights unusual FMP development and gives a novel clue to antenatal diagnosis and management.
Keywords: abdominal cyst; meconium peritonitis; fetoscopic laser photocoagulation; complications; meconium pseudocyst